2015
DOI: 10.1039/c4tc02955k
|View full text |Cite
|
Sign up to set email alerts
|

Aza-boron-diquinomethene complexes bearing N-aryl chromophores: synthesis, crystal structures, tunable photophysics, the protonation effect and their application as pH sensors

Abstract: A series of new aza-boron-diquinomethene complexes (1a–1e) with tunable photophysical properties has been designed and synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…Zhu and co‐workers have designed new aza–boron–diquinomethene complexes 103 a – e containing different N ‐arylamines (see Figure ). Photoluminescence studies reveal that all of the probes show an intense and tunable luminescence signal from blue to red and good emission quantum yields.…”
Section: Red Fluorescent Dyesmentioning
confidence: 99%
“…Zhu and co‐workers have designed new aza–boron–diquinomethene complexes 103 a – e containing different N ‐arylamines (see Figure ). Photoluminescence studies reveal that all of the probes show an intense and tunable luminescence signal from blue to red and good emission quantum yields.…”
Section: Red Fluorescent Dyesmentioning
confidence: 99%
“…compounds 139 and 140 displayed relatively large Stokes shifts (34-51 nm) as compared to the typical BODIPY dyes; such molecular scaffolds can be used to develop fluorescence probes in future. Zhu et al (2015) have prepared very interesting BF 2 complexes 141 and 142 (Chart 27); where the aza-dipyrromethene skeleton was replaced by the aza-boron-diquinomethene. The aza-borondiquinomethene scaffold was substituted with N-carbazolyl and/or 3,6-di-tert-butyl-N-carbazolyl moieties (Chart 27); the photoluminescence spectra of 141 and 142 showed greenyellow emission due to intramolecular charge transfer.…”
Section: Miscellanious Systemsmentioning
confidence: 99%
“…The aza-borondiquinomethene scaffold was substituted with N-carbazolyl and/or 3,6-di-tert-butyl-N-carbazolyl moieties (Chart 27); the photoluminescence spectra of 141 and 142 showed greenyellow emission due to intramolecular charge transfer. The fluorescence quantum yields were reasonably high between 0.73 and 0.78; such BF 2 complexes may be suitable for developing pH-sensors and bioimaging probes in future (Zhu et al, 2015). Ema et al have reported a series of exciting BF 2 complexes based on carbazole scaffold (Maeda et al, 2016); where carbazole ring was substituted with thiazole, benzothiazole, imidazole, indolone, and benzimidazole (Chart 28).…”
Section: Miscellanious Systemsmentioning
confidence: 99%
“…我们在前期 工作中研究发现四苯基并吡咯(DPPTP)对三氯甲烷有荧 光淬灭的响应, 原因是三氯甲烷在光照条件下分解成氯 化氢气体与 DPPTP 相互作用使其荧光淬灭 [14] . DPPDC [15] .…”
Section: Dppdc 的酸响应行为unclassified